Interpersonal Fairness, Willingness-to-Stay and Organisation-Based Self-Esteem: The Mediating Role of Affective Commitment - Tetteh, Samuel Doku; Osafo, Joseph; Ansah-Nyarko, Michael; Amponsah-Tawiah, Kwesi (Frontiers in Psychology, 2019)
This study examines the direct and indirect effects of interpersonal fairness on employees’ willingness-to-stay and organisation-based self-esteem through affective commitment among manufacturing workers in Tema, Ghana. Using the survey design, 300 manufacturing workers in Tema were conveniently sampled for the study. The confirmatory factor analysis and structural equation modelling were used to analyse the data. Results indicated that affective commitment partially mediated the relationship between interpersonal fairness and employees' willingness-to-stay. Affective commitment also fully mediated the interpersonal fairness- organisation based self-esteem relationship. Results further showed that organisation based self-esteem partially mediated the affective commitment and willingness to stay relationship, such that, an increase in organisation-based self-esteem leads to a decrease in employees’ willingness-to-stay. These findings emphasised the roles of interpersonal fairness and affective commitment in organisations, where affective commitment increases as a result of an increase in interpersonal fairness and makes employees have an intention to stay. The findings imply that employees who are very confident and have higher organisation-based self-esteem stand lower chances of staying in their current organisations. This study is the first to examine how affective commitment transfers the effects of interpersonal fairness unto employees’ intention-to-stay among manufacturing workers in Ghana.